A surfactant‐based wound dressing can reduce bacterial biofilms in a porcine skin explant model. Issue 2 (22nd May 2016) - Yang, Qingping; Larose, Christelle; Della Porta, Alessandra C; Schultz, Gregory S; Gibson, Daniel J
Abstract: Bacterial biofilms have been found in many, if not all, chronic wounds. Their excessive extracellular matrix secretion and the metabolic changes that they undergo render them highly tolerant of many antibiotic and antimicrobial treatments. Physical removal and/or disruption are a common approach to treating wounds suspected of having bacterial biofilms. While many of these techniques use mechanical energy as the primary means of removal, we have begun to investigate if surfactants could facilitate the removal of bacterial biofilms, or if they might sensitise the biofilms to antimicrobial interventions. We tested a new surfactant‐based wound gel on an ex vivo porcine skin explant model infected with a functionally tolerant 3‐day biofilm. The wounds were dressed with a surfactant‐based gel directly on the wound or with moistened gauze. The wounds were then wiped daily with moistened gauze, and the gel or gauze was re‐applied. Each day, an explant from each group was harvested and tested for total viable bacteria counts and viable biofilm‐protected bacteria counts. The results show that daily wiping with moistened gauze led to an initial decrease of bacteria, but by day 3, the biofilm had been fully re‐established to the same level prior to the beginning of treatment. For the surfactant‐based treatment, there was no detectable functional biofilm after the first treatment. The gauze control, which was also subjected to daily wiping, still contained functional biofilms, indicating that this result was not due to wiping alone. The total bacteria in the surfactant‐treated explants steadily decreased through day 3, when there were no detectable bacteria, while the wiping‐only control bacteria counts remained steady. The use of a moist gauze to wipe the visually apparent slime off of a wound appears to be insufficient to reduce biofilm over a 3‐day period. Daily application of the surfactant gel dressing and wiping reduced the biofilm to undetectable levels within 3 days in a skin explant model. A 3‐day regimen of dressing the wound model with a surfactant gel followed by gentle removal of the gel by wiping with a moistened gauze appears to be a simple and adequate approach to removing a bacterial biofilm infection in an ex vivo model. Additional clinical evidence is needed to determine if this promising approach can perform the same in clinically infected chronic wounds.